Multimedia push system based on a wellness slot machine. (28th April 2020) - Chang, Yi-Chun; Li, Jian-Wei; Lin, Chia-Ching; Yang, Fu-Syuan
In an aged society, more than 80% of elders who are still healthy or sub-healthy people with self-care abilities, sociability and the society support system should access mental care which can be effectuated in a play therapy program. Based on electronic games supplemented by a media push system, the wellness slot machine practised in this study is a play therapy platform through which a preventive care service program for recreational effects and health promotion is planned for elders. For necessary information available to elderly participants of wellness slot machines such as ads for community activities and promotional films naturally and constantly, the multimedia push system in this study is designed and practised in a wellness slot machine with which the media content is pushed to the elderly participants actively without excessive manual operations.